A SEMIOTIC ANALYSIS OF RACE DISCRIMINATION IN THE FALCON AND THE WINTER SOLDIER - Vionny Lydia Puspita; Marginingsih Marginingsih (Universitas Duta Bangsa Surakarta, 2024)
Racism is one of the endless global issues, from the past until now the issue of racism has brought a lot of sadness. The Falcon and The Winter Soldier series tells about discrimination from various races, especially discrimination against the black race in America. This research was conducted to find out how various aspects of racism are depicted in The Falcon and The Winter Soldier series. The method used is Roland Barthes' semiotic analysis with two-stage signification, namely denotation-connotation and myth. The results of this study show that there are depictions of various aspects of racism in The Falcon and The Winter Soldier series. There are racial prejudice, racial stereotypes, racial discrimination, and racial violence. Although the racism depicted in The Falcon and The Winter Soldier miniseries is subtle and occurs in various walks of life, it can be fatal.